The teaching practice in the binational center (Ecuador - Peru) of technical formation Zapotepamba of the National University of loja - Vacacela Ajila, Wilmer (2015)
The research had as objective to know the teaching practice, regarding methodologies of teaching- learning strategies and the evaluation of the learnings that have been used in the technology race production and agricultural extension, where studying high school graduates of the north of Peru and the southern of Ecuador , and even the Galapagos Archipelago. This study was developed under the focus of teaching current alternative critical because priority was the analysis of the development of potentialities and capacities. (Cognitive and educational).The independent variables were: innovative strategies for teaching and learning; the mechanisms for evaluating the programming, and the dependent variable was the teaching practice. It is analyzed for the entire student population composed of 53 students, of whom 36.56 % were women and 63.44 % are men. The applied study was correlational, and the data obtained were analyzed according to the recommendations of the descriptive statistics. The verification of the assumption was made by the Pearson's Chi-square test (X2); determining that there is statistical relationship between the teaching practice and innovative strategies in teaching and learning, as well as among the teaching practice and assessment mechanisms in the programming. Teaching practice is considered as good by the experience of teachers and the teaching strategies - applied learning, such as audiovisual media, the problem-based learning and the educational projects productive. With regard to the methodologies of evaluation there are weaknesses that should be you think institutionally.